2007
DOI: 10.1097/01.ncq.0000263110.38591.9a
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Pediatric Nursing Care in Finland

Abstract: This study assessed the quality of pediatric nursing care as perceived by children (N = 388) aged 7 to 11 in Finland. The children rated as excellent the nursing environment, the nurses' humanity and trustworthiness, and caring and communication. They were most critical about the nurses' entertainment activities such as playing with them. Children's age and type of admission were both related to the amount of information they received. The instrument used in the study needs to be developed and tested further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 30 publications
4
31
2
10
Order By: Relevance
“…These findings parallel those of previous studies . Moreover, the defects in handling the education process noted in this study were consistent with studies reporting on educational needs that were not met as well as lack of parent participation and child participation .…”
Section: Discussionsupporting
confidence: 92%
“…These findings parallel those of previous studies . Moreover, the defects in handling the education process noted in this study were consistent with studies reporting on educational needs that were not met as well as lack of parent participation and child participation .…”
Section: Discussionsupporting
confidence: 92%
“…Pelander et al (2007) and Pelander and Leino-Kilpi (2004) confirmed that the parents' presence contributes to the child's feeling of safety as well as making treatments more easily accepted. Gimbler-Berglund et al (2008) emphasize that it is the parents who have the greatest knowledge about the child.…”
Section: Discussionsupporting
confidence: 66%
“…2004). Provision of better communication, through both verbal and non‐verbal ways is one way to deliver appropriate care and to help the child adjust to stress of hospitalisation (Pelander et al. 2007b).…”
Section: Introductionmentioning
confidence: 99%